2012
DOI: 10.1055/s-0039-1698942
|View full text |Cite
|
Sign up to set email alerts
|

Hardness, polymerization depth, and internal adaptation of Class II silorane composite restorations as a function of polymerization protocol

Abstract: Objectives:To evaluate the influence of various photoactivation techniques on the internal gap, Knoop-hardness, and polymerization depth of silorane- and methacrylate-based composites in Class II restorations.Methods:Preparations were made in third molars (n = 10), according to composites (Filtek P60: methacrylate; Filtek P90: silorane) and photoactivation techniques (OC: occlusal photoactivation (control); OBL: occlusal+buccal+lingual photoactivation; and BLO: buccal+lingual+occlusal photoactivation (transden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…Another important consideration in the results of this study is a better marginal seal of cavities restored with silorane-based composite resin compared to dimethacrylate-based composite resin, consistent with the results of studies by Bechtold et al, 36 Nanjundasetty et al, 37 Krifka et al 38 and Bin Hasan and AL Saif, 39 who reported a better performance of silorane-based composite resins in terms of marginal adaptation. However, Arslan et al 12 did not report any differences between these two composite resin types, which was attributed to the nano-filled nature of the used dimethacrylate-based composite resin.…”
Section: Discussionsupporting
confidence: 89%
“…Another important consideration in the results of this study is a better marginal seal of cavities restored with silorane-based composite resin compared to dimethacrylate-based composite resin, consistent with the results of studies by Bechtold et al, 36 Nanjundasetty et al, 37 Krifka et al 38 and Bin Hasan and AL Saif, 39 who reported a better performance of silorane-based composite resins in terms of marginal adaptation. However, Arslan et al 12 did not report any differences between these two composite resin types, which was attributed to the nano-filled nature of the used dimethacrylate-based composite resin.…”
Section: Discussionsupporting
confidence: 89%
“…39 The samples in group 4 underwent a bleaching procedure with LED light at a light intensity over 1000 mW/cm 2 ; therefore, it is hypothesized that curing percentage of composite resins increased during bleaching under the effect of this light intensity; an increase in curing percentage results in an increase in polymerization of composite resin, which in itself increases microhardness. 40 This phenomenon compensates a decrease in composite resin microhardness due to bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the microhardness is the indirect methods to verify DC characterizing the monomer conversion, hardness values do not always predict the DC in comparisons of different resin materials. Despite of similar DC, 3-D structures of polymerized composite with different concentrations of C=C bonds can coexist in the same polymer structure 31. Also, microhardness can be influenced by monomer phase and filler phase.…”
Section: Discussionmentioning
confidence: 99%